IMPLEMENTASI PEMBERIAN PENGUATAN (VERBAL DAN NON VERBAL) OLEH GURU KELAS II SD AN NAMIROH PEKANBARU - Dewi, Ratna; Witri, Gustimal; Putra, Zetra Hainul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this study was to describe the implementation of the teacher in providing verbal and non-verbal reinforcement to the second grade students of SD An Namiroh Pekanbaru. The subjects of this study were class IIA, IIB, IIC teachers. The data collection techniques used by this researcher were through observation, interviews and documentation study. observations made by the researcher were 3 meetings in each class. The data analysis used in this research is descriptive qualitative. The results showed that grade II teachers of SD An Namiroh Pekanbaru had tried to implement reinforcement. Verbal reinforcement is done by giving appreciation or praise to students' behavior with words or sentences of praise by paying attention to the principle of giving reinforcement. The implementation of non-verbal reinforcement is done by providing touches, approaches, fun activities, symbols or objects, and partial reinforcement to students.Key Words: Verbal and Non Verbal Reinforcement, Teacher